Cloggs Cave pollen sequences, GunaiKurnai Country, East Gippsland (SE Australia): 25,000 years of cultural plant use and changing environments - Grono, Elle; David, Bruno; Stevenson, Janelle; Fresløv, Joanna; Mullett, Russell; Keaney, Benedict; Graham, Catriona; Ash, Jeremy; , GunaiKurnai Land; Waters Aboriginal Corporation; McDowell, Matthew C.; Petchey, Fiona; et al. (Frontiers in Environmental Archaeology, 2024)
In southeastern Australia, GunaiKurnai caves are known by current Aboriginal Elders and from nineteenth century ethnographic documents as special places used by mulla-mullung (“clever men” and “clever women”) for the practice of magic and medicine. Pollen analysis conducted on sediments from one such cave, Cloggs Cave, reveals an unusually well-preserved and well-stratified pollen sequence extending back >25,000 years, with much of the pollen introduced into the cave by people carrying flowering plants. High concentrations of pollen, rare for limestone cave settings, were recovered, including pollen clumps of individual taxa representing deposition of in situ flowering material. These taxa are dominated by plants known through GunaiKurnai knowledge and ethnography to have special cultural uses and that match the plants known to have been used by mulla-mullung, and some edible plants. These include taxa such as Banksia spp., Pimelea spp. (rice flower), and Plantago spp. (plantain) and the plant families of Asteraceae (daisy) and Poaceae (grass). The largely anthropogenic pollen assemblage also signals the presence of plants from cooler and drier climates dominated by more open vegetation during the Last Glacial Maximum than that observed around Cloggs Cave in recent times. The Early Holocene pollen then reflects a warmer and wetter climate that supported the expansion of woodland elements. Together, the pollen record of Cloggs Cave provides remarkable insights into two articulating histories: the cultural practices of the GunaiKurnai Old Ancestors in a special, secluded cave; and the environmental history of Country.